Values of Football Referees - Özer Yıldız; Mehtap Yıldız (Selcuk University, 2020)
Almost every team that has been defeated in recent years has indicated football referees as the first guilty, and the public pressure on the referees managing the competitions is increasing. Despite these adverse conditions, it is considered important to determine what values the football referees have to manage the competitions. The aim of this research is to determine the value orientation of football referees. The research group consisted of 35 male football referees actively refereeing in the 2019-2020 Football Season in Turkey. Research data was obtained through semi-structured interview method. The data were evaluated by content analysis method. As a result of the research, various values were reached in social, personal, morals, belief, culture, extraversion, sensing, thinking, feeling, judging categories. Keywords: Values, Football, Referee